Donor risk factors, retrieval technique, preservation and ischemia/reperfusion injury in pancreas transplantation. - Maglione, M; Ploeg, R; Friend, P (2013)
PURPOSE OF REVIEW: Pancreas transplantation is still hampered by a high incidence of early graft loss, and organ quality concerns result in high nonrecovery/discard rates. Demographic donor characteristics, surgical retrieval strategy, preservation fluid and ischemia time are crucial factors in the process of organ selection and are discussed in this review. RECENT FINDINGS: The donor shortage is driving an increasing utilization of nonideal organs which would previously have been identified as unsuitable. Recent literature suggests that organs from extended criteria donors - older (>45 years), BMI >30  kg/m(2), and donation after cardiac death (DCD) - can achieve the same graft and patient survival as those from standard criteria donors, with the proviso that the accumulation of risk factors and long ischemic times should be avoided. Visual assessment of the pancreas is advisable before declining/accepting a pancreas. University of Wisconsin represents the gold standard solution; however, histidine-tryptophan-ketoglutarate and Celsior result in equal outcomes if cold ischemia time (CIT) is less than 12  h. Currently in pancreas transplantation, there is no proven effective ischemia/reperfusion injury prophylaxis than trying to keep CIT as short as possible. SUMMARY: Demographic risk factors, inspection of the pancreas by an experienced surgeon and predicted CIT are crucial factors in deciding whether to accept a pancreas for transplantation. However, there is a need for an improved evidence base to determine where to set the 'cut-off' for unsuitable pancreatic grafts.